Structural design of core-shell zeolitic imidazolate frameworks as an efficient catalyst for CO2 cycloaddition to epoxides. (April 2023) - Nguyen, Que Thi; Jeong, Keunhong; Lee, Yu-Ri; Baek, Kyung-Youl
Abstract: Size-controlled hybrid ZIFs (core-shell ZIF-67@ZIF-8, ZIF-8@ZIF-67, and bimetallic Zn/Co-ZIF-8) with the same particle size were synthesized by a seed-mediated methodology by adjusting the particle size of core ZIFs. The synthesized hybrid ZIFs was tested as heterogeneous catalysts for the CO2 cycloaddition to epoxides using pure CO2 gas and mixed gas (85 % CO2 /15% N2 ) without any co-catalyst and solvent. The effect of the composition of shell and core ZIFs on the catalytic performance of CO2 cycloaddition reaction to epoxides were investigated. Furthermore, the correlation between structural defects and catalytic activity in ZIF catalysts along with their particle sizes was investigated by calculating the ratio of DXRD/DSEM. Both core-shell type ZIF-67@ZIF-8 and ZIF-8@ZIF-67 exhibited better catalyst performance of CO2 cycloaddition reaction than other ZIF catalysts. Among the ZIF catalysts, ZIF-67@ZIF-8 exhibited the highest catalytic performance for epoxide conversion owing to its abundant Lewis acid-base properties and relatively large window size of ZIF-8 shell with appropriate binding force between epoxide and CO2 . It showed good recyclability for CO2 cycloaddition reaction without a structural collapse during ten recycles. The structural stability of ZIF-67@ZIF-8 was examined in detail by a hot filtering test, leaching test, and TGA analysis. The mechanism of CO2 cycloaddition reaction was proposed and the effect of the shell composition in core-shell type ZIFs on the binding energy with epoxide substrate also was studied based on DFT calculations. Graphical Abstract: ga1 Highlights: Synthesis of size-controlled core-shell ZIFs by a seed-mediated methodology. Investigating the effect of the core-shell ZIF structures on the catalytic activity. ZIF-67@ZIF-8 exhibits high catalytic activity for CO2 cycloaddition reaction. The correlation between structural defects and catalytic activity in ZIF catalysts. Calculation of binding energy with epoxide and core-shell ZIFs using DFT method.